A blinded comparison of fluticasone propionate with budesonide via powder devices in adult patients with moderate-to-severe asthma: a clinical evaluation. Issue 5 (1996) - Ringdal Ringdal, N. N.; Swinburn Swinburn, P. P.; Backman Backman, R. R.; Plaschke Plaschke, P. P.; Sips Sips, A. P. A. P.; Kjaersgaard Kjaersgaard, P. P.; Bratten Bratten, G. G.; Harris Harris, T. A. J. T. A. J.
Abstract : In Vitro and in vivo data have demonstrated that there are detectable differences between inhaled corticosteroids commonly used to treat asthma. However, controversy still remains as to whether these differences translate into clinical benefits. This 12-week, international, randomized, doubleblind, parallel-group study was undertaken to compare the efficacy and safety of fluticasone propionate (FP) 800 μg daily, administered as a powder via the Diskhaler ®, and budesonide (BUD) 1600 μg daily, administered using the Turbuhaler ®, in adult patients with moderate-tosevere asthma. A total of 518 patients participated in the study, 256 of whom received FP and 262 BUD. Assessment of mean morning peak expiratory flow (PEF) over the 12-week treatment period revealed a statistically significant difference in efficacy between FP 800 μg daily and BUD 1600 μg daily in favour of FP ( p = 0.003), with an overall improvement of 20.9 l/min with FP compared with 12.4 l/min on BUD. Statistically significant differences in favour of FP were seen over the 12 weeks for mean evening PEF ( p = 0.04), diurnal PEF variation ( p = 0.03) and percentage predicted PEF ( p = 0.003), as well as forced expiratory volume ( p = 0.008), forced vital capacity ( p = 0.02) and PEF ( p = 0.005) measured at clinic visits. The median percentage of symptom-free nights increased over the 12-week study period in both treatment groups, with similar changes seen for the median percentage of days with symptom score < 2, rescue medication use and exacerbations of asthma. The incidence of adverse events was found to be comparable in the two treatment groups. The geometric mean ratios of serum cortisol levels were found to be 1.03 for FP, indicating no mean hypothalamic-pituitary-adrenal axis suppression from baseline, and 0.93 for BUD ( p = 0.0002 compared with FP). In summary, FP 800 μg daily showed a greater efficacy/safety ratio in the treatment of moderate-to-severe asthma than BUD 1600 μg daily.